Maternal and Cord Blood Vitamin B12, Folate and Homocysteine Levels - Selime Özen Bölük; Ebru Şahin; Oya Baltalı Halıcıoğlu; Feyza Koç; Sadık Aksit (Journal of Pediatric Research, 2022)

(untitled)
Aim:Nowadays, insufficiency and deficiency of vitamin B12 and folate are seen as an important health problem. The purpose of the present study was to determine the frequency of vitamin B12 and folate deficiencies in pregnant women and their babies at birth.Materials and Methods:The study group consisted of 117 pregnant women and their single, term babies in İzmir Ege Maternity Hospital. Analysis of vitamin B12, folate and homocysteine levels were performed from venous blood samples which were obtained from the mother and cord blood at birth. Additionally, a questionnaire using a face-to-face interview method was performed with the pregnant women included in this study. The mean duration of pregnancy was 39.1±0.89 weeks and the mean age of the mothers was 28.2±6.2 years.Results:Vitamin B12 deficiency (<130 pg/mL) was present in 88.9% of mothers and 56% of babies. Folate deficiency (<4 ng/mL) was found in 6.8% of mothers, but not found in any babies. The homocysteine levels were high (>8 µmol/L) in 58.1% of mothers and 63.2% of babies. There was a significant correlation between maternal and cord blood vitamin B12, folate and homocysteine levels (p<0.01). However, there was no correlation between maternal vitamin B12 and homocysteine levels (p=0.016, p=0.354).Conclusion:Low maternal vitamin B12 levels are strongly associated with low cord blood vitamin B12 levels. This data reveals that vitamin B12 deficiency which can occur from the neonatal period is a preventable public health problem. Pregnant women and physicians should be made aware of the importance of vitamin B12 intake during pregnancy.